PENGARUH PEMASARAN DIGITAL DAN PERDAGANGAN ELEKTRONIK TERHADAP VOLUME PENJUALAN DI KOTA PRABUMULIH - Tusri, Yudi; Handayani, Tri Ana; Gultom, Angga Wibowo (Bussman Journal : Indonesian Journal of Business and Management, 2024)
This research aims to determine the influence of digital marketing (X?) and electronic commerce (X?) partially and simultaneously on sales volume (Y) at Queen Galeri in Prabumulih City with a sample of 115 respondents who are consumers at Queen Galeri in Prabumulih City. The method used in this research is a descriptive analysis with a quantitative approach and a questionnaire. The analysis technique used is multiple linear regression analysis created with SPSS version 26. The results of statistical testing show that the digital marketing variable (X?) partially has a positive and significant effect on sales volume (Y) with a value of count> table or 5,844 > 1,981, with a substantial value of 0.000 < 0.05. The electronic commerce variable (X?) partially has a positive and significant effect on sales volume (Y) with a value of count> table or 3,298 > 1,981, with a substantial value of 0.000 < 0.05. Simultaneous testing shows that Fcount > Ftable or table 0.841 > 3.08 with a significant value of 0.000 < 0.05. So it can be concluded that there is a positive and considerable influence of digital marketing variables (X?) and electronic commerce (X?) of bouquets simultaneously on sales volume (Y) at Queen Galeri in Prabumulih City. Based on the summary model output, a determination test table gives an Adjusted R Square of 0.486. This means that 48.6% of sales volume is influenced by digital marketing and electronic commerce, while the remaining 51.4% is influenced by other variables not examined in this research such as location, facilities, and services at Queen Galeri in Prabumulih City